2014
DOI: 10.1098/rspb.2013.2797
|View full text |Cite
|
Sign up to set email alerts
|

Specific non-monotonous interactions increase persistence of ecological networks

Abstract: The relationship between stability and biodiversity has long been debated in ecology due to opposing empirical observations and theoretical predictions. Species interaction strength is often assumed to be monotonically related to population density, but the effects on stability of ecological networks of non-monotonous interactions that change signs have not been investigated previously. We demonstrate that for four kinds of non-monotonous interactions, shifting signs to negative or neutral interactions at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 51 publications
0
41
0
Order By: Relevance
“…In the non-monotonic models with two interacting species, Zhang (2003) defined 11 possible equilibrium points. As compared to monotonic models, non-monotonic functions can increase species coexistences by producing stable equilibrium or reducing unstable equilibrium (Yan and Zhang, 2014, also see below).…”
Section: Non-monotonicity Between Speciesmentioning
confidence: 95%
See 4 more Smart Citations
“…In the non-monotonic models with two interacting species, Zhang (2003) defined 11 possible equilibrium points. As compared to monotonic models, non-monotonic functions can increase species coexistences by producing stable equilibrium or reducing unstable equilibrium (Yan and Zhang, 2014, also see below).…”
Section: Non-monotonicity Between Speciesmentioning
confidence: 95%
“…Through simulation, Yan and Zhang (2014) found that four kinds of non-monotonic functions, shifting signs to negative or neutral interactions at high population density (Fig. 5d-f and i) increases persistence of ecological networks.…”
Section: Non-monotonicity In Ecosystemsmentioning
confidence: 95%
See 3 more Smart Citations